Обоюдоострый меч деколонизации и осуждения геноцида - Мелик-Багдасарян, Геворк; Сарьян, Асатур (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Հայոց ցեղասպանութեան 110-րդ տարելիցի եւ լեհ մեծանուն մարդասէր Բոգդան Գեմբարսկու ծննդեան 120-ամեակի կապակցութեամբ հրապարակւում է հայ ժողովրդի նուրիրեալ բարեկամի, ազնիւ մարդու եւ մտաւորականի թղթերից մէկը՝ «Նամակ իմ հայ ընթերցողներին »։ Ցայսօր Բոգդան Գեմբարսկու՝ Հայ դատին եւ Հայոց հարցին նուիրուած ոչ բոլոր գրուածքներն են հրատարակուել ։ Մինչդեռ ոչ միայն դրանց հրատարակումը, այլեւ թարգմանութիւնն ու տարածումը պէտք է լինէր յետանկախական շրջանի մեր կարեւորագոյն եւ առաջնային քայլերից ։ Ներկայացուած նամակը հիմք է հանդիսացել այլալեզու թարգմանութիւնների համար, բայց ռուսերէն տարբերակով տակաւին չէր դրուել շրջանառութեան մէջ, ուստի հեղինակները փորձում են լրացնել այդ բացը ։ In commemoration of the 110th anniversary of the Armenian Genocide and the 120th birthday of the esteemed Polish humanitarian Bogdan Gembarski, we present one of the letters from this devoted friend of the Armenian people—a man of profound integrity and intellect—A Letter to My Armenian Readers. To this day, many of Bogdan Gembarski’s writings dedicated to the Armenian Genocide and the Armenian Question remain unpublished. Yet, their publication, translation, and widespread dissemination should have been among the most vital and urgent priorities of the post-independence era. This letter has served as a foundation for translations into other languages; however, until now, the Russian version had not been made available. The authors, therefore, seek to bridge this gap.
Keywords: Армянский геноцид; Богдан Гембарский